Actor‐network analysis of community‐based organisations in health pandemics: evidence from the COVID‐19 response in Freetown, Sierra Leone. Issue 4 (13th July 2022) - Frimpong, Louis Kusi; Okyere, Seth Asare; Diko, Stephen Kofi; Abunyewah, Matthew; Erdiaw‐Kwasie, Michael Odei; Commodore, Tracy Sidney; Hernandez, Daniel Oviedo; Kita, Michihiro
Abstract : Freetown, Sierra Leone, is confronted with health risks that are compounded by rapid unplanned urbanisation and weak capacities of local government institutions. Addressing them implies a shared responsibility between government and non‐state actors. In low‐income areas, the role of community‐based organisations (CBOs) in combating health disasters is well‐recognised. Yet, empirical evidence on how they have utilised their networks and coordinated community‐level strategies in responding to the COVID‐19 pandemic is scant. This paper, based on a qualitative study in two informal settlements in Freetown, employs actor‐network theory to understand how CBOs problematise COVID‐19 as a health risk, interact with other entities, and the subsequent tensions that arise. The findings show that community vulnerabilities and past experiences of health disasters informed CBOs' perception of COVID‐19 as a communal emergency. In response, they coordinated sensitisation and mobilisation programmes by relying on a network of actors to support COVID‐19 risk reduction strategies. Nonetheless, misunderstandings among them caused friction. Abstract : نبذة مختصرة تواجه فريتاون مخاطر صحية تتفاقم بفعل التحول الحضري غير القائم على التخطيط، وضعف قدرات مؤسسات الحكومة المحلية. يتطلب التصدي لمثل هذه المخاطر الصحية المجتمعية مسؤولية مشتركة بين جهات فاعلة حكومية، وجهات فاعلة غير حكومية. يكون دور المنظمات المجتمعية، في المجتمعات منخفضة الدخل، بشأن مكافحة الكوارث الصحية أمراً معترفاً به تماماً. ومع ذلك، فإن الأدلة التجريبية، بشأن الكيفية التي تنتفع بها المنظمات المجتمعية من شبكاتها، ومن تنسيق الاستراتيجيات على مستوى المجتمع في التصدي لمرض فيروس كورونا المستجد، أدلة ضئيلة. استناداً إلى دراسة نوعية على مستوطنتين غير رسميتين في فريتاون، تعتمد هذه الورقة على نظرية شبكة الجهات الفاعلة لفهم كيفية تعامل المنظمات المجتمعية مع مرض فيروس كورونا المستجد، بوصفه خطراً صحياً، والتفاعل مع الجهات الفاعلة الأخرى، والتوترات التي تنشأ داخل شبكات الجهات الفاعلة هذه. تظهر نتائج الدراسة أن نقاط الضعف المجتمعية، والتجارب السابقة مع الكوارث الصحية، مثل الإيبولا، هي التي شكلت شكلت تصوراً للمنظمات المجتمعية عن مرض فيروس كورونا المستجد على أنه حالة طوارئ مجتمعية. استجابةً لذلك، نسّقت المنظمات المجتمعية برامج توعية وتعبئة من خلال الاعتماد على شبكة جهات فاعلة داخلية وخارجية لدعم استراتيجيات الحد من مخاطر مرض فيروس كورونا المستجد. ومع ذلك، تسبب سوء الفهم بين الجهات الفاعلة في توترات في شبكة الجهات الفاعلة. تقترح الدراسة أن إنشاء قنوات جديدة لتبادل المعرفة والبناء بشأن قدرة المنظمات المجتمعية، يمكن أن يساعد على تعزيز شبكات الجهات الفاعلة في المجتمعات، ومكافحة الكوارث الصحية الحالية والمستقبلية. عبارات محورية: نظرية الجهات الفاعلة والشبكة، منظمة مجتمعية، مرض فيروس كورونا المستجد، فريتاون، كارثة صحية، استجابات محلية Abstract : 摘要 弗里敦遇到跟公共卫生相关的风险，由于快速而无秩序的城镇化和地方政府机构的薄弱能力，这个问题变得更加复杂。应对这类社区公共卫生风险意味着政府和非政府行动者之间要承担共同的责任。在低收入社区，基于社区的组织（CBOs）在抗击公共卫生灾害中的角色得到了大家的赞同。然而，基于社区的组织如何利用其网络及协调社区层面的战略，以应对新冠疫情，这方面的实践经验的证明还很少。根据对弗里敦两个非正式定居点的定性研究，本文通过行动者‐网络理论，解释基于社区的组织如何将新冠疫情变成公共卫生风险的须解决的问题，跟其他行动者互动，同时，应对这些行动者网络中产生的紧张状况。研究结果表明，社区的弱势和以往应对埃博拉等公共卫生灾害的经验，由此得到的信息使基于社区的组织将新冠疫情视为社区紧急情况。作为响应，基于社区的组织依赖内部和外部行动者的网络，以支持新冠疫情风险弱化的战略，该组织通过这种方法协调增敏和调动方案。不过，行动者之间的误解造成行动者‐网络中的紧张状况。该研究建议，建立新的知识交流渠道，并提升基于社区的组织的能力，有助于加强社区内的行动者网络，以及抗击当前及未来的公共卫生灾害。 关键词：行动者‐网络理论、基于社区的组织、新冠病毒、弗里敦、公共卫生灾害、地方响应